Two new species of Aphelochaeta (Annelida: Polychaeta: Cirratulidae) from Korean waters - Choi, Hyun Ki; Jung, Tae Won; Yoon, Seong Myeong (Zootaxa, 2018)
Two new cirratulid polychaetes of the genus Aphelochaeta collected from Korean waters are reported here along with detailed descriptions and illustrations. Aphelochaeta petila n. sp. is readily distinguished from its congeners by the following characteristics: non-expanded anterior and posterior ends of the body; non-moniliform segments in the abdomen; peristomium with three annulations and an indistinct dorsal crest; both the dorsal tentacles and the first branchiae attached on the peristomium; presence of only a pair of branchiae on chaetiger 1; and the ventrum of the thoracic region with transverse dark blue stripes on the chaetigers 6–16 with methyl green staining. Aphelochaeta intinctoria n. sp. is characterized by a combination of the following features: a rounded prostomium; a peristomium with a dorsal crest; a non-expanded thoracic region; dorsal tentacles on the peristomium and the first pair of branchiae on chaetiger 1; and the thoracic region lacking a distinct methyl green staining pattern. These two new species from Korean waters also differ in details of chaetal ultrastructure.